THE INFLUENCE OF ONLINE VIDEO PLATFORMS ON INFORMATION AND COMMUNICATION CONSUMPTION - St. Wijdanah Ram; Nur Aina Ahmad (Adisam Publisher, 2025)
Online video platforms have changed the way information is consumed and communication is conducted in the digital age. The ease of access and variety of content allows users to gain knowledge from multiple perspectives, transcending the limitations of traditional media. Video as a communication medium enhances visual and auditory message delivery, making it more effective and immersive. However, the adoption of this platform also poses challenges such as the spread of hoaxes and a potential decrease in time for other activities. Therefore, users need to be more selective in filtering information and balancing online video consumption time with other activities for healthy digital wellbeing.